PENGARUH STRATEGI GIVING QUESTION AND GETTING ANSWER TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Putri, Rahmi Elza; Rahmi, Rahmi; Edriati, Sofia (STKIP PGRI Sumatera Barat, 2018)
AbstractThe aim of this research is to know whether the math students’ learning outcomes by implementing active learning strategy typed giving question and getting answer are better than the math students’ learning outcomes by implementing conventional learning. The design of this research is experimental research by random design to the subject. The population of the research is the eighth grade students of SMP Muhammadiyah 6 Padang in academic year 2017/2018 that consist of three classes. Then, the sampling technique is done randomly. As a result, Class VIII 3 is as experimental class and VIII 2 is as control class. The instrument used in this research is the essay test. The technique of data analysis is using t-test in one class. Based on the result of data analysis can be concluded that the math students’ learning outcomes by implementing active learning strategy typed giving question and getting answer are better than the math students’ learning outcomes by implementing conventional learning.